Influence of Wearing a Tactical Harness on Three-Dimensional Thoracic Limb Kinematics - Sandberg, Gabriella S.; Pawloski, Thomas; Kang, Sean; Banu, Eliza; Torres, Bryan T.; Budsberg, Steven C. (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective The aim of this study was to assess the impact of a tactical harness on three-dimensional motion of the thoracic limb in dogs.Animals Five adult mixed-breed dogs (age: 4–6 years, weight: 25–35 kg) were used in this study.Methods Custom-fit tactical harnesses were applied to each dog and 19 retroreflective skin markers were used to determine three-dimensional joint motion during dynamic motion, with and without the harness. Sagittal plane (flexion–extension), transverse plane (internal–external rotation), and frontal plane (abduction–adduction) kinematics were created for the shoulder, elbow, and carpus from motion capture data, with and without the harness. Kinematic waveforms were analysed using statistical parametric mapping paired t-tests (a = 0.05). Angular displacements were determined, and total joint range of motion was compared using paired t-tests (a = 0.05).Results Wearing a tactical harness increased sagittal angular displacement in the elbow but decreased it in the shoulder and carpus. Significant differences were found in the kinematic waveforms in almost all joints at both a walk and trot. Dogs wearing the tactical harness had reduced flexion and increased abduction of the shoulder joint at a walk. The elbow joint had increased extension, reduced external rotation and increased abduction at both walk and trot. The carpus had reduced flexion at a trot and walk, as well as increased internal rotation and abduction at a walk.Conclusion Wearing a tactical harness affected kinematic gait data of all joints of the forelimb. The elbow was affected in all three planes at both a walk and trot, while the shoulder joint was only affected at a walk when wearing a tactical harness.Clinical Relevance The clinical impact of wearing a tactical harness is unknown at this time, particularly when dogs are performing their duties while wearing harnesses.
Keywords: gait analysis; joint angular displacements; joint motion; kinematics; Dog